Pola Konsumsi Berisiko dan Sosio-Demografi Sebagai Faktor Resiko Penyakit Hipertensi - Arrafi Insani; Dina Zairina Rizky; Erishta Khofifah Barus; Fira Wulandari; Linda Syafitri Siagian; Sri Ramadhani (Sarana Ilmu Indonesia (salnesia), 2021)
Hypertension is the third largest disease in Aek Kuasan District, The high prevalence of hypertension can be caused by so many factors such as sociodemography and risky dietary patterns. The purpose of this study was to determine the hypertension risk factors based on socio-demographic and risky dietary patterns. This study used a descriptive-analytic method with a cross-sectional study design which was carried out in July-August 2021 in Aek Loba Afdeling 1 village. A total of 184 participants of age 18-80 were selected, taken by random sampling. The results showed that the prevalence of hypertension was 37%. There was a significant relationship between being aged ?60 years old (P<0,05, AOR; 5,976, 95% CI;2,13-16,7), excessive salt consumption (P<0.05, AOR; 2,226, 95% CI; 1,03-4,76), frequent consumption of instant noodles (P<0.05, AOR; 2,956, 95% CI; 1,34-4,79), frequent consumption of preserved foods (P<0.05, AOR; 4,511, 95% CI; 1,89-10,7), and frequent consumption of red meat (P<0,05 , AOR;2,411, 95% CI: 1,44-3,93) with hypertension. The conclusion of this study is that main factors of hypertension on this research is being aged ?60 years old. Suggestions for health workers to be able to increase promoting health and screening activities, especially for the elderly.